MENINGKATKAN SAINS PERMULAAN UNTUK ANAK USIA DINI DENGAN PEMANFAATAN MEDIA HERBARIUM - Ranny Fitria Imran; Rika Partikasari; Iit Sektian Jahniar (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This research was conducted in RA Babul Jannah Bengkulu City. This study conducted a qualitative descriptive study. Data collection techniques used are observation, interviews, and documentation. The purpose of this study is to develop science for early childhood by using herbarium media at 5-6 years old in RA Babul Jannah Bengkulu City. Based on the results of this study it can be concluded that early childhood science through herbarium media in RA Babul Jannah Bengkulu City increased, with categories starting to develop (MB) there were 3 children with a percentage rate of 25%, the category developed according to expectations (BSH) there were 3 children with a percentage rate of 25%, including the category of developing very well (BSB) there are 9 children with a percentage rate of 50%.